Google Earth forensics : using Google Earth geo-location in digital forensic investigations - Harrington, Michael (Writer on mobile device forensics); Cross, Michael, 1965- (Syngress, 2015)
This book explains how to use Google Earth in digital forensic investigations. This book teaches you how to leverage Google's free tool to craft compelling location-based evidence for use in investigations and in the courtroom. It shows how to e.